PENGEMBANGAN MODUL KAULINAN BARUDAK LEMBUR UNTUK MENINGKATKAN MOTIVASI BELAJAR PAI DI SEKOLAH DASAR - Hendrayana, Deni; Wicaksono, Dirgantara (Penerbit Widina, Widina Media Utama, 2025)
This study highlights the importance of Islamic Religious Education (PAI) in shaping the character of young generations, particularly in rural areas facing challenges such as low student learning motivation. The research aims to develop the